Rare earth element modification method for aluminide cladding coating

By introducing rare earth elements and NH4Cl into the aluminide coating and adopting laser cladding process, the problem of the oxidation resistance of existing coatings decreased after long-term service is solved, and coating preparation with high oxidation performance and peeling resistance is achieved, which is suitable for complex shape workpieces.

CN119824407APending Publication Date: 2025-04-15XIAN THERMAL POWER RES INST CO LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411892245.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

After the existing aluminide coatings are in service for a long time, the oxidation resistance decreases and film peeling occurs, resulting in a decrease in oxidation resistance and making it difficult to meet the needs of complex shape workpieces such as large length-to-diameter ratios.

Method used

A rare earth element modification method for aluminide cladding coating was used to prepare a coating with high oxidation performance by adding NH4Cl, Ce and Y to the slurry and combined with laser cladding technology.

Benefits of technology

It improves the oxidation resistance and peeling resistance of the coating, enhances the stability and oxidation resistance of the coating, and is suitable for complex shape workpieces such as large length-to-diameter ratios, and has high process repeatability and high production efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119824407A_ABST
    Figure CN119824407A_ABST
Patent Text Reader

Abstract

The invention discloses a rare earth element modification method of an aluminide cladding coating, which comprises the following steps: mixing a solid-phase component and a binder, then carrying out ball milling to obtain cladding slurry, cleaning and preheating a workpiece, coating the cladding slurry on the workpiece, then carrying out air drying and curing, and then carrying out laser cladding, wherein the solid phase component comprises 60 to 80 percent of FeAl, 15 to 30 percent of Al, 2 to 7 percent of NH4Cl and 0 to 5 percent of Ce and Y; and the binder is ethyl acetate. According to the invention, the infiltration speed and the coating quality are improved; rare earth modified elements Ce and Y are introduced into the solid-phase powder, so that the conversion process of an oxidation film can be promoted, outward diffusion of the Al element is hindered, the stability of the coating is improved, and the oxidation and corrosion resistance of the coating is enhanced; the coating is prepared through the laser cladding technology, the technology is concentrated in heat, short in acting time, small in heat influence of a cladding area, and high in bonding strength of the coating and base metal; the coating is prepared through the integrated laser cladding process production line, the production efficiency of the coating is high, the thickness is controllable, the process repeatability is high, and the practicability and the universality are extremely high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of material surface alloying and coating preparation, and specifically relates to a rare earth element modification method for an aluminide cladding coating. Background Art

[0002] In the thermal power generation industry, pipe blockage and pipe burst accidents caused by oxidation of the inner wall of the flow pipe account for more than 50% of the non-stop accidents of the boiler, resulting in an increase of more than 20% in the operating cost and material cost of the unit, which has become a common industry problem and technical pain point that restricts the safe production and operation of the entire energy equipment. In response to this problem, Xi'an Thermal Engineering Institute has developed a high-temperature anti-oxidation coating preparation technology suitable for the large aspect ratio structural characteristics, high temperature, long time, and low stress service environment characteristics of the flow components of energy equipment, mainly based on aluminide coatings; in the actual unit operation test, the aluminide coating also showed excellent anti-oxidation service performance. However, with the extension of service time, the increase of unit power, and the complexity of the service environment, a single aluminide coating will inevitably face the phenomenon of decreased oxidation resistance and film peeling. In addition, after long-term service, the Al element content of the film layer decreases, and the density and uniformity of the oxide film will also be lost, reducing the anti-oxidation performance of the coating; therefore, it is necessary to develop a new type of anti-oxidation coating preparation technology and process with excellent oxidation resistance and anti-stripping ability, suitable for various complex-shaped workpieces with large aspect ratios. Summary of the invention

[0003] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.

[0004] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.

[0005] Therefore, the object of the present invention is to overcome the deficiencies in the prior art and provide a rare earth element modification method for an aluminide cladding coating.

[0006] In order to solve the above technical problems, the present invention provides the following technical solutions: comprising: mixing the solid phase component with the binder and then ball milling to obtain a cladding slurry, cleaning the workpiece and preheating it, applying the cladding slurry to the workpiece and then air drying and curing it, and then performing laser cladding;

[0007] The solid phase components include 60-80% FeAl, 15-30% Al, 2-7% NH4Cl and 0-5% Ce and Y; the binder is ethyl acetate.

[0008] As a preferred embodiment of the preparation method of the present invention, the mass ratio of the solid phase component to the binder is 1:0.1-0.3.

[0009] As a preferred embodiment of the preparation method of the present invention, the solid phase component needs to be ball-milled at 350-400 rpm for 12-24 hours.

[0010] As a preferred embodiment of the preparation method of the present invention, the binder needs to be ball-milled at 350-400 rpm for 8-12 hours.

[0011] As a preferred embodiment of the preparation method of the present invention, the cleaning is performed by washing with a high-pressure water gun and rinsing with alcohol.

[0012] As a preferred embodiment of the preparation method of the present invention, the preheating treatment is medium frequency preheating at 200-250°C for 30-60 minutes.

[0013] As a preferred solution of the preparation method of the present invention, the coating thickness is 1 to 5 mm, and the coating coverage is not less than 98%.

[0014] As a preferred embodiment of the preparation method of the present invention, the air-drying time is 24 to 48 hours.

[0015] As a preferred embodiment of the preparation method of the present invention, the curing treatment is performed at 300 to 450° C. for 24 to 48 hours.

[0016] As a preferred embodiment of the preparation method described in the present invention, the laser cladding has a laser power of 2 to 2.8 kW, a scanning rate of 20 to 40 mm / s, a spot diameter of 3 to 5 mm, a workpiece rotation speed of 0 to 5 r / min, and an Ar gas flow rate of 15 to 20 L / min.

[0017] Beneficial effects of the present invention:

[0018] (1) The present invention adds halide NH 4 Cl plays a role in promoting infiltration and activation, improving the infiltration rate and coating quality; introducing rare earth modifying elements Ce and Y into the solid phase powder can promote the transformation process of the oxide film, hinder the outdiffusion of Al elements, improve the stability of the coating, and enhance the oxidation and corrosion resistance of the coating; the coating is prepared by laser cladding process, which has concentrated heat, short action time, small thermal impact in the cladding area, and high bonding strength between the coating and the parent material; the coating is prepared by an integrated laser cladding process production line, with high coating production efficiency, controllable thickness, high process repeatability, and extremely strong practicality and universality.

[0019] (2) The present invention introduces Ce element modification, which can promote the oxide film transformation process and accelerate the θ-Al 2 O 3 To α-Al 2 O 3 The transformation of the film base can improve the bonding strength and optimize the antioxidant performance; the introduction of Y element modification can hinder the internal diffusion of oxygen atoms and the external diffusion of aluminum atoms, and delay the occurrence of oxidation behavior; natural air drying combined with medium and low temperature slurry curing process can effectively avoid the micro cracks and tiny holes in the slurry layer caused by thermal stress during direct drying, and enhance the bonding strength between the slurry layer and the workpiece surface. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:

[0021] Figure 1 This is the cross-sectional morphology of the rare earth element modified aluminide cladding coating in Example 1 of the present invention. DETAILED DESCRIPTION

[0022] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.

[0023] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.

[0024] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.

[0025] Unless otherwise specified, the raw materials used in the examples of the present invention are commercially available.

[0026] Example 1

[0027] (1) Weigh the solid phase components according to mass ratio, including 60% FeAl, 30% Al, 3% Ce, 5% Y and 2% NH 4Cl, place it in a planetary ball mill at 400 rpm for 12 hours to obtain solid phase cladding powder; then, add 10% ethyl acetate and stir it for 4 hours, then place it in a planetary ball mill at 400 rpm for 12 hours, and after completion, obtain a uniformly mixed slurry, which is the cladding slurry.

[0028] (2) Clean the workpiece surface with a high-pressure water gun for 5 minutes and rinse it with alcohol or acetone; then, preheat the workpiece at 250°C for 45 minutes using medium frequency, and use spraying to pre-set the slurry layer thickness to 3 mm, maintaining the coating coverage rate not less than 98%; then, air dry the workpiece naturally for 48 hours and cure it at 300-450°C for 48 hours.

[0029] (3) The workpiece was placed under Ar for laser cladding, with a laser power of 2 kW, a scanning rate of 40 mm / s, a spot diameter of 3 mm, a workpiece rotation speed of 6 r / min, and an Ar gas flow rate of 15 L / min. After completion, the workpiece was cooled to room temperature and the residue on the surface of the workpiece was washed away with high-pressure airflow.

[0030] Example 2

[0031] The difference from Example 1 is that in step (3), the laser power is 2.8 KW, the scanning rate is 30 mm / s, the spot diameter is 3 mm, the workpiece rotation speed is 5 r / min, and the Ar gas flow rate is 15 L / min.

[0032] Example 3

[0033] The difference from Example 1 is that in step (3), the laser power is 2.8 KW, the scanning rate is 20 mm / s, the spot diameter is 5 mm, the workpiece rotation speed is 4 r / min, and the Ar gas flow rate is 15 L / min.

[0034] Example 4

[0035] The difference from Example 1 is that in step (3), the laser power is 2.8 KW, the scanning rate is 25 mm / s, the spot diameter is 4 mm, the workpiece rotation speed is 4 r / min, and the Ar gas flow rate is 20 L / min.

[0036] Example 5

[0037] The difference from Example 1 is that in step (3), the laser power is 2.5 KW, the scanning rate is 30 mm / s, the spot diameter is 3 mm, the workpiece rotation speed is 2 r / min, and the Ar gas flow rate is 18 L / min.

[0038] Example 6

[0039] The difference from Example 1 is that in step (3), the laser power is 2.4 KW, the scanning rate is 25 mm / s, the spot diameter is 4 mm, the workpiece rotation speed is 2 r / min, and the Ar gas flow rate is 15 L / min.

[0040] Example 7

[0041] The difference from Example 1 is that in step (3), the laser power is 2.8 KW, the scanning rate is 35 mm / s, the spot diameter is 3 mm, the workpiece rotation speed is 5 r / min, and the Ar gas flow rate is 20 L / min.

[0042] Example 8

[0043] The difference from Example 1 is that in step (3), the laser power is 2.6 KW, the scanning rate is 25 mm / s, the spot diameter is 3 mm, the workpiece rotation speed is 4 r / min, and the Ar gas flow rate is 18 L / min.

[0044] Example 9

[0045] The difference from Example 1 is that in step (3), the laser power is 2.8 KW, the scanning rate is 40 mm / s, the spot diameter is 4 mm, the workpiece rotation speed is 4 r / min, and the Ar gas flow rate is 20 L / min.

[0046] After the aluminide coating samples prepared in Examples 1 to 9 were ground with #280-#2000 sandpaper and mechanically polished, the microscopic morphology of the samples was observed using a scanning electron microscope (SEM, ZEISS SIGMA 300, Germany), and the average thickness of the diffusion layer was measured using Image J software.

[0047] Table 1 Laser cladding process parameters and infiltration layer thickness in Examples 1 to 9

[0048]

[0049] By analyzing and studying the above examples, the thickness of the infiltration layer is measured to be about 0.22-1.45 mm. The specific results are shown in Table 1. The typical coating cross-sectional morphology is as follows Figure 1 As shown in Table 1 and the cross-sectional morphology, it is found that the diffusion layer has a uniform structure, moderate thickness, sufficient diffusion of Al atoms, and a good metallurgical bond between the diffusion layer and the matrix, and is not easy to fall off.

[0050] Example 10

[0051] (1) Weigh the solid phase components according to mass ratio, including 80% FeAl, 15% Al, 1% Ce, 1% Y and 3% NH 4Cl, place it in a planetary ball mill at 350 rpm for 24 hours to obtain solid phase cladding powder; then, add 30% ethyl acetate and stir it for 2 hours, then place it in a planetary ball mill at 400 rpm for 12 hours, and after completion, a uniformly mixed slurry is obtained, which is the cladding slurry.

[0052] (2) Clean the workpiece surface with a high-pressure water gun for 5 minutes and rinse it with alcohol or acetone; then, preheat the workpiece at 200°C for 60 minutes, and use spraying to pre-set the slurry layer thickness to 5 mm, keeping the coating coverage rate not less than 98%; then, air dry the workpiece naturally for 24 hours and cure it at 300°C for 48 hours.

[0053] (3) The workpiece was placed under Ar for laser cladding with a laser power of 2.5 kW, a scanning rate of 20 mm / s, a spot diameter of 2 mm, a workpiece rotation speed of 5 r / min, and an Ar gas flow rate of 15 L / min. After completion, the workpiece was cooled to room temperature and the residue on the surface of the workpiece was washed away with high-pressure airflow.

[0054] Embodiment 11

[0055] (1) Weigh the solid phase components according to mass ratio, including 65% FeAl, 25% Al, 5% Y and 5% NH 4 Cl, place it in a planetary ball mill at 400 rpm for 24 hours to obtain solid phase cladding powder; then, add 20% ethyl acetate and stir it for 2 hours, then place it in a planetary ball mill at 350 rpm for 8 hours, and after completion, a uniformly mixed slurry is obtained, which is the cladding slurry.

[0056] (2) Clean the workpiece surface with a high-pressure water gun for 5 minutes and rinse it with alcohol or acetone; then, preheat the workpiece at 250°C for 30 minutes using medium frequency, and use spraying to pre-set the slurry layer to a thickness of 2 mm, maintaining a coating coverage of not less than 98%; then, air dry the workpiece naturally for 24 hours and cure it at 450°C for 48 hours.

[0057] (3) The workpiece was placed under Ar for laser cladding, with a laser power of 2.8 kW, a scanning rate of 40 mm / s, a spot diameter of 3 mm, a workpiece rotation speed of 2 r / min, and an Ar gas flow rate of 15 L / min. After completion, the workpiece was cooled to room temperature and the residue on the surface of the workpiece was washed away with high-pressure airflow.

[0058] Example 12

[0059] (1) Weigh the solid components according to mass ratio, including 65% FeAl, 25% Al, 5% Ce and 5% NH 4Cl, place it in a planetary ball mill at 400 rpm for 12 hours to obtain solid phase cladding powder; then, add 20% ethyl acetate and stir it for 2 hours, then place it in a planetary ball mill at 350 rpm for 12 hours, and after completion, obtain a uniformly mixed slurry, which is the cladding slurry.

[0060] (2) Clean the workpiece surface with a high-pressure water gun for 5 minutes and rinse it with alcohol or acetone; then, preheat the workpiece at 200°C for 60 minutes, and use spraying to pre-set the slurry layer thickness to 5 mm, keeping the coating coverage rate not less than 98%; then, air dry the workpiece naturally for 24 hours and cure it at 400°C for 48 hours.

[0061] (3) The workpiece was placed under Ar for laser cladding, with a laser power of 2.8 kW, a scanning rate of 20 mm / s, a spot diameter of 3 mm, a workpiece rotation speed of 5 r / min, and an Ar gas flow rate of 15 L / min. After completion, the workpiece was cooled to room temperature and the residue on the surface of the workpiece was washed away with high-pressure airflow.

[0062] Example 13

[0063] (1) The solid phase components were weighed according to the mass ratio, including 60% FeAl, 25% Al, 3% Ce, 5% Y and 7% NH 4 Cl, place it in a planetary ball mill at 400 rpm for 24 hours to obtain solid phase cladding powder; then, add 30% ethyl acetate and stir it for 2 hours, then place it in a planetary ball mill at 400 rpm for 12 hours, and after completion, a uniformly mixed slurry is obtained, which is the cladding slurry.

[0064] (2) Clean the workpiece surface with a high-pressure water gun for 5 minutes and rinse it with alcohol or acetone; then, preheat the workpiece at 250°C for 45 minutes using medium frequency, and use spraying to pre-set the slurry layer thickness to 5 mm, maintaining the coating coverage rate not less than 98%; then, air dry the workpiece naturally for 24 hours and cure it at 450°C for 48 hours.

[0065] (3) The workpiece was placed under Ar for laser cladding, with a laser power of 2 kW, a scanning rate of 30 mm / s, a spot diameter of 5 mm, a workpiece rotation speed of 5 r / min, and an Ar gas flow rate of 18 L / min. After completion, the workpiece was cooled to room temperature and the residue on the surface of the workpiece was washed away with high-pressure airflow.

[0066] Embodiment 14

[0067] (1) Weigh the solid phase components according to mass ratio, including 70% FeAl, 20% Al, 2% Ce, 5% Y and 3% NH 4Cl, place it in a planetary ball mill at 350 rpm for 12 hours to obtain solid phase cladding powder; then, add 30% ethyl acetate and stir it thoroughly for 4 hours, then place it in a planetary ball mill at 400 rpm for 8 hours, and after completion, a uniformly mixed slurry is obtained, which is the cladding slurry.

[0068] (2) The workpiece surface is cleaned with a high-pressure water gun for 5 minutes and rinsed with alcohol or acetone; then, the workpiece is preheated at 250°C for 60 minutes by medium frequency, and the slurry layer thickness is pre-set to 4 mm by spraying, and the coating coverage is maintained at not less than 98%; then, the workpiece is naturally air-dried for 36 hours and cured at 450°C for 48 hours.

[0069] (3) The workpiece was placed under Ar for laser cladding, with a laser power of 2.8 kW, a scanning rate of 40 mm / s, a spot diameter of 5 mm, a workpiece rotation speed of 4 r / min, and an Ar gas flow rate of 20 L / min. After completion, the workpiece was cooled to room temperature and the residue on the surface of the workpiece was washed away with high-pressure airflow.

[0070] Embodiment 15

[0071] (1) Weigh the solid phase components according to mass ratio, including 75% FeAl, 15% Al, 3% Ce, 3% Y and 4% NH 4 Cl, place it in a planetary ball mill at 350 rpm for 24 hours to obtain solid phase cladding powder; then, add 20% ethyl acetate and stir it thoroughly for 4 hours, then place it in a planetary ball mill at 400 rpm for 8 hours, and after completion, a uniformly mixed slurry is obtained, which is the cladding slurry.

[0072] (2) The workpiece surface is cleaned with a high-pressure water gun for 5 minutes and rinsed with alcohol or acetone; then, the workpiece is preheated at 250°C for 60 minutes by medium frequency, and the slurry layer thickness is pre-set to 5 mm by spraying, and the coating coverage is maintained at not less than 98%; then, the workpiece is naturally air-dried for 48 hours and cured at 450°C for 48 hours.

[0073] (3) The workpiece was placed under Ar for laser cladding, with a laser power of 2.8 kW, a scanning rate of 40 mm / s, a spot diameter of 4 mm, a workpiece rotation speed of 4 r / min, and an Ar gas flow rate of 15 L / min. After completion, the workpiece was cooled to room temperature and the residue on the surface of the workpiece was washed away with high-pressure airflow.

[0074] Example 16

[0075] (1) The solid phase components were weighed according to the mass ratio, including 65% FeAl, 20% Al, 5% Ce, 5% Y and 5% NH 4Cl, place it in a planetary ball mill at 400 rpm for 24 hours to obtain solid phase cladding powder; then, add 30% ethyl acetate and stir it for 4 hours, then place it in a planetary ball mill at 400 rpm for 8 hours, and after completion, a uniformly mixed slurry is obtained, which is the cladding slurry.

[0076] (2) The workpiece surface is cleaned with a high-pressure water gun for 5 minutes and rinsed with alcohol or acetone; then, the workpiece is preheated at 250°C for 60 minutes by medium frequency, and the slurry layer thickness is pre-set to 5 mm by spraying, and the coating coverage is maintained at not less than 98%; then, the workpiece is naturally air-dried for 24 hours and cured at 450°C for 48 hours.

[0077] (3) The workpiece was placed under Ar for laser cladding, with a laser power of 2.8 kW, a scanning rate of 35 mm / s, a spot diameter of 4 mm, a workpiece rotation speed of 2 r / min, and an Ar gas flow rate of 18 L / min. After completion, the workpiece was cooled to room temperature and the residue on the surface of the workpiece was washed away with high-pressure airflow.

[0078] The anti-oxidation performance of the infiltration layers prepared in Examples 10 to 16 in 600° C. water vapor was tested. The test results are shown in Table 2.

[0079] High temperature steam oxidation test: Place the aluminide coating sample in the constant temperature area of ​​a constant temperature tube furnace. When the temperature in the tube furnace reaches the test temperature of 650°C, continuous water vapor is introduced into the reaction furnace through the water vapor generator at the front end. The test is carried out for 200, 300, 500, and 800 hours, and the sample is taken out and weighed with an electronic balance with an accuracy of 0.01 mg.

[0080] Table 2 Mass change of the infiltrated layer prepared in Examples 10 to 16 in 600°C steam (mg / cm 2 )

[0081]

[0082] Comparative Example 1

[0083] The difference from Example 15 is that the halide is NH 4 I.

[0084] Comparative Example 2

[0085] The difference from Example 15 is that the halide is NH 4 Br.

[0086] Comparative Example 3

[0087] The difference from Example 15 is that the solid phase components are replaced by 75% FeAl, 15% Al, 6% Ce and 4% NH 4 Cl.

[0088] Comparative Example 4

[0089] The difference from Example 15 is that the solid phase components are replaced by 75% FeAl, 15% Al, 6% Y and 4% NH 4 Cl.

[0090] Comparative Example 5

[0091] The difference from Example 15 is that the solid phase components are replaced by 75% FeAl, 15% Al, 6% La and 4% NH 4 Cl.

[0092] Comparative Example 6

[0093] The difference from Example 15 is that the binder is polyvinyl alcohol.

[0094] Comparative Example 7

[0095] The difference from Example 15 is that the curing temperature is 300°C.

[0096] Table 3 Mass changes of the infiltrated layers prepared in Example 15 and Comparative Examples 1 to 7 in 600°C steam (mg / cm 2 )

[0097]

[0098] Figure 1 This is the cross-sectional morphology of the rare earth element modified aluminide cladding coating in Example 1 of the present invention.

[0099] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the present invention.

Claims

1. A rare earth element modification method for an aluminide cladding coating, characterized in that: The process includes mixing a solid phase component with a binder and then ball milling to obtain a cladding slurry, cleaning the workpiece and then preheating it, applying the cladding slurry to the workpiece and then air drying and solidifying it, and then performing laser cladding; The solid phase components include 60-80% FeAl, 15-30% Al, 2-7% NH4Cl and 0-5% Ce and Y; the binder is ethyl acetate.

2. The rare earth element modification method according to claim 1, characterized in that: The mass ratio of the solid phase component to the binder is 1:0.1-0.

3.

3. The rare earth element modification method according to claim 2, characterized in that: The solid phase components need to be ball-milled at 350-400 rpm for 12-24 hours.

4. The rare earth element modification method according to claim 2, characterized in that: The binder needs to be ball-milled at 350-400 rpm for 8-12 hours.

5. The rare earth element modification method according to claim 1, characterized in that: The cleaning is performed by using a high-pressure water gun and rinsing with alcohol.

6. The rare earth element modification method according to claim 1, characterized in that: The preheating treatment is medium frequency preheating at 200-250° C. for 30-60 minutes.

7. The rare earth element modification method according to claim 1, characterized in that: The coating thickness is 1 to 5 mm, and the coating coverage is not less than 98%.

8. The rare earth element modification method according to claim 1, characterized in that: The air-drying time is 24 to 48 hours.

9. The rare earth element modification method according to claim 1, characterized in that: The curing treatment is performed at 300 to 450° C. for 24 to 48 hours.

10. The rare earth element modification method according to claim 7, characterized in that: The laser cladding has a laser power of 2 to 2.8 KW, a scanning rate of 20 to 40 mm / s, a spot diameter of 3 to 5 mm, a workpiece rotation speed of 0 to 5 r / min, and an Ar gas flow rate of 15 to 20 L / min.

Citation Information

Patent Citations

  • Preparation process of Cr-Al-Ce-Y thermal protective coating on surface of titanium and aluminum alloy and penetrant thereof

    CN107779813A

  • Preparation method of obdurability high-temperature steam oxidation resistant coating

    CN113802088A

  • Method for improving corrosion resistance of aluminide cladding coating

    CN118726971A

  • Rare earth element modified aluminide cladding coating and preparation method thereof

    CN118756132A